An overview of African livestock genetic resources and improvement strategies - Ibeagha-Awemu, E.M.; Peters, S.O.; Djikeng, Appolinaire; Rege, J.E.O. (Springer, 2025)
This book is the first comprehensive text that presents the rich livestock genetic resources in Africa in one volume. This introductory chapter summarizes the materials covered in the book. It introduces the various topics covered and serves as a guide to topics of interest.